Microfacies Analysis and Stratigraphic Evolution of Garagu Formation in Selected Oil Fields, Northern Iraq - Mahdi, Fatima Ali; Al-Zaidy, Aiad Ali Hussien (Iraqi Journal of Science, 2024)
The Garagu Formation represents a part of the Late Tethonian-Middle Valanginian sequence, which was deposited during the Early Cretaceous period within the main carbonate open marine environment. The studied area covers three oil fields; Jambur (Ja-46), Khabaz (Kz-1), and Qara Chauq (Qc-2) oil fields which are located in the north part of Iraq within the Low Folded Zone.Eight major microfacies were recognized in Garagu Formation within the area of study to determination and recognition the paleoenvironments. The major microfacies for this carbonate succession are; Lime mudstone microfacies, Orbitolinid and Nezzazata wackestone with bioclast microfacies, Foraminifera wackestone-packstone microfacies, Bioclast wackestone – packstone microfacies, Algal wackestone-packstone with bioclast microfacies, Oolitic packstone-grainstone with bioclast microfacies, Coral bioclast packstone - grainstone microfacies, Planktonic wackestone-packstone microfacies and Peloidal (pellets) packstone -grainstone microfacies. These microfacies are deposited in restricted marine, shoal and open marine, Mid ramp, and outer ramp associations facies.The Garagu succession in the studied area is divided into two depositional cycles (C1 and C2) of highstand system tracts (HST) in Ja-46 well. In the Khabaz oil field (Kz-1), the succession is divided into three cycles of HST (C1, C2, and C3). While in the Qara Chuaq oil field (Qc-2) the succession is divided into four depositional cycles of HST (C1, C2, C3, and C4) with conformable underlying Makhul Formation and conformable overlying of Ratawi Formation. In both oil fields, the Sarmord Formation is conformable underlying of Garagu Formation and conformable overlying of Ratawi Formation.